Assessment of Quality and Chemical Composition of Cajuput Oil from Moluccas and Papua - S. Idrus; M. S. Radiena; . Sumarsana; H. Smith (Newest Updates in Physical Science Research Vol. 1, 2021)
Melaleuca leucadendron Linn is a type of cajuput oil producer was found in the Moluccas are mostly on the Buru Island and West Seram, while Asteromyrtus brasii is a type that is found in Wasur National Park, Merauke, Papua. The main product of cajuput plants is cajuput oil that obtained from distillation of cajuput leaves. The main markets for cajuput oil include The United States, Japan, Singapore, France and the Netherlands. This study aims to decide on the chemical content and physical properties of cajuput oil that distilled from Melaleuca leucadindron leaves from Moluccas and A. brasii which grow in meet Wasur National Park. Analysis of the chemical content of essential oils was carried out using the Gas Chromatography and Mass Spectrometer method. Physical properties analysis was carried out using the method according to SNI 06-3954-2006. The test results showed that the quality of cajuput oil from Melaleuca leucadendron the SNI 06-3954-2006 standard, while type A. brasii did not meet the quality requirements based on SNI 06-3954-2006. The results obtained from the test using the GCMS method showed that there were 26 peaks with the highest peak being 1.8 cineole. The content of 1.8 cineole from Central of Moluccas at 55.22%, Buru Island at 61.69%, West Barat at 70.22% and Wasur National Park at 34.88%.